Phylogenomic analyses reveal a Palaeozoic radiation and support a freshwater origin for clitellate annelids - Erséus, Christer; Williams, Bronwyn W.; Horn, Kevin M.; Halanych, Kenneth M.; Santos, Scott R.; James, Samuel W.; Creuzé des Châtelliers, Michel; Anderson, Frank E. (Zoologica scripta, 2020)
Clitellata is a major clade of Annelida comprising nearly all freshwater and terrestrial annelids as well as several marine species. We investigated clitellate phylogenetic relationships using transcriptomes sampled from 74 taxa (64 clitellates and 10 polychaetes), including multiple representatives of nearly all major clitellate higher taxa (Branchiobdellida, Capilloventridae, Crassiclitellata, Enchytraeidae, Haplotaxidae, Hirudinida, Lumbriculida, Moniligastridae, Naididae, Parvidrilidae, Phreodrilidae, Propappidae and Randiellidae). We used a number of filtered data matrices and phylogenetic analyses to examine the effects of data partitioning, missing data and compositional and branch‐length heterogeneity and used the resulting phylogenies for divergence time estimation and ancestral habitat reconstructions. All analyses and filtering methods produced a consistent, strongly supported topology in which (a) Enchytraeidae, Hirudinida, Hirudinea (here, Branchiobdellida plus Hirudinida), Lumbriculida, Lumbriculata (Lumbriculida plus Hirudinea), Phreodrilidae and Naididae are monophyletic, (b) a Parvidrilidae + Randiellidae clade is sister to the rest of Clitellata, (c) Phreodrilidae is sister to Naididae, (d) Haplotaxidae is non‐monophyletic, with some haplotaxids grouping with Crassiclitellata + Moniligastridae, (e) the Phreodrilidae + Naididae clade is sister to all other clitellates except Parvidrilidae + Randiellidae and Capilloventridae, and (f) Lumbriculata is sister to the Crassiclitellata + Moniligastridae + Haplotaxidae (in part) clade. Ancestral habitat reconstructions and divergence time analysis suggested that the most recent common ancestor of Clitellata lived in freshwater during the Devonian (419–359 million years ago) and that all major extant clitellate lineages arose over the next ~150 million years, with multiple lineages subsequently returning to marine habitats or invading land. This study provides a phylogenetic framework for further investigation of the geological, environmental and biotic forces and genomic changes that may have impacted clitellate evolution and enabled several major habitat transitions within this group.